2016
DOI: 10.48550/arxiv.1605.02356
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moduli spaces of flat tori and elliptic hypergeometric functions

Selim Ghazouani,
Luc Pirio

Abstract: In the genus one case, we make explicit some constructions of Veech [76] on flat surfaces and generalize some geometric results of Thurston [71] about moduli spaces of flat spheres as well as some equivalent ones but of an analytico-cohomological nature of Deligne and Mostow [11], which concern Appell-Lauricella hypergeometric functions. 2 S. GHAZOUANI AND L. PIRIOTable of Contents 1. Introduction 2 2. Notations and preliminary material 23 3. Twisted (co-)homology and integrals of hypergeometric type 26 4. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(257 reference statements)
1
0
0
Order By: Relevance
“…These connections suggest that twisted de Rham theory could provide a unified and robust framework to comprehend genus-one string integrals, their reductions, monodromy relations, and open-closed string relations [1-4, 27, 76-91]. Existing mathematical frameworks that leverage twisted cohomology setups have already demonstrated that meromorphic Kronecker-Eisenstein series form a basis under certain conditions, and a generalization of this could substantiate the conjectures presented herein [37,46,47,[92][93][94][95].…”
Section: Jhep05(2024)255 10 Discussionsupporting
confidence: 61%
“…These connections suggest that twisted de Rham theory could provide a unified and robust framework to comprehend genus-one string integrals, their reductions, monodromy relations, and open-closed string relations [1-4, 27, 76-91]. Existing mathematical frameworks that leverage twisted cohomology setups have already demonstrated that meromorphic Kronecker-Eisenstein series form a basis under certain conditions, and a generalization of this could substantiate the conjectures presented herein [37,46,47,[92][93][94][95].…”
Section: Jhep05(2024)255 10 Discussionsupporting
confidence: 61%